Development and Testing of Mobile Assisted Language Learning Application to Improve Oral Clinical Case Presentation of Student Nurses - Cynthia Milton; Aruna Subramaniam; S. Sridevi; S. Ganesh Kumar (International Journal of Interactive Mobile Technologies (iJIM), 2023)
Background: Nurses’ oral case presentation is a core clinical communication skill with distinctivelinguistic qualities that require specific language training. The present paper is auser feedback analysis of a start-up Mobile Assisted Language Learning application (MALLapp) developed and implemented to provide English language training to improve OralCase Presentation (OCP) of student nurses pursuing baccalaureate degrees from a nursingcollege in South India. Objective: The aim was to develop and test an Android based OCPMALLapplication for user acceptability and effectiveness in improving OCP performanceand decreasing the perceived language difficulty. Methodology: Sixty-two student nursesfrom a reputed nursing college in Chennai, South India, using Android mobile phonesparticipated in the study. All the participants were given access and instructions on theuse of OCP-MALL app. A comparison of pre and post-test of perceived level of languagedifficulty and OCP pre and post score along with users’ acceptance were collected. Results:The users’ acceptability showed that all participants rated the clarity in reading the textwith highest mean score of 8.29 and std of 1.276, simplicity in navigation – moving to nextpage with next highest mean score of 8.19 and std of 1.526, clarity in text application layoutwith a mean score of 8.14 and std of 1.497 and user friendliness of the application witha mean score of 8.13 and std of 1.393. Conclusion: This startup OCP-MALL app user satisfactionfeedback proves that